Psikoedukasi pola hidup bersih sehat pada siswa di lingkungan Rumah Belajar Kakek Aboe, Malang - Dimas Setyadi Putra (Altruis: Journal of Community Services, 2022)
COVID-19 is a disease caused by SARS-CoV-2, as of March 24, 2022 in Indonesia, a total of 5,986,830 confirmed positive patients and 3,266 people came from East Java. Knowledge and actions from the public regarding PHBS are able to reduce the number of COVID-19 cases so that it will accelerate the end of a pandemic. Knowledge is the forerunner of behavior which is the main reason or motivation for a person to behave. This service was carried out on 27 July – 09 September 2020 through an educative approach in the form of exposure to COVID-19 transmission material, good hand washing, proper use of masks and other Clean and Healthy Lifestyles (PHBS). Questionnaires were used to measure students' knowledge. It is known that there was an increase in the average score from the pretest of 8.63 to 8.93, which means that there was an increase in students' knowledge in Rumah Belajar Kakek Aboe after being given education